Adams and Victor's principles of neurology - Ropper, Allan H; Brown, Robert H; Adams, Raymond D; Victor, Maurice (McGraw-Hill, 2005)
A new take on the classic, definitive text on the full spectrum of neurology. Reflecting a modern approach to neurology, Adams and Victors Principles of Neurology, 8/e new format highlights a more complete and accessible approaches to treatment and clinical management strategies. This thoroughly revised edition features more coverage of treatment and neuroimaging, renown signs and symptoms sections integrated throughout, and over 800 illustrations.
Keywords: Neuroglia; neuroglie; neurologie